Sistem Pendukung Keputusan Rekomendasi Beasiswa dengan Metode Moora Studi Kasus: MTs Muhammadiyah 1 Kec. Dukun - Ferdian Ferdian; Umi Chotijah (Universitas Islam Lamongan, 2022)
Scholarship provision is a financial assistance program from the school agency to underprivileged students or students. MTS Muhammadiya 1 Dukun has a financial assistance program for students who are less well off financially. In the selection process for the acceptance of the MTS Muhammadiya 1 Dukun scholarship program, manual calculations are still used. Based on the current scholarship selection system, it is certainly less effective and efficient. A Decision Support System is used at MTS Muhammadiya 1 Dukun to help with the process of choosing students who are qualified for the scholarship program. The decision support system for the scholarship program's admission is created using PHP, the Bootstrap framework, and a MySQL database. the procedure for applying the MOORA technique to obtain the selection outcomes based on predefined criteria. The academic success index gleaned from report cards, parents' income, and the number of dependent parents are the factors considered. The decision support system developed in this study has the ability to provide the ranking of the selection results and identify students who are recommended for the scholarship program or who are qualified based on preset criteria.